PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA BISNIS (Studi Kasus Pada Toko Roti Panggang Banjar di Sawah Lebar Kota Bengkulu) - Adi Sismanto; Furqonti Ranidiah; Anggun Tarisa (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTBusiness performance is a common factor used to measure the import of a company’s strategy on dealing with competition. To improve performance, companies must conduct market orientation and innovation in order to survive in existing competition. The purpose of this study was to determine the effect of market orientation and product innovation on business performance at Banjar Toast Shop in Sawah Lebar, Bengkulu. This study used survey research methods with quantitative data analysis. The population in this study were consumers at Banjar Toast Shop in Sawah Lebar, Bengkulu and the sampling used a total sampling method, amounting to 100 people. Based on the results of multiple linier regression, the regression equation is Y = 0.754+0.779 () + 0.265 (). Research results and hypotheses indicate that market orientation () has a significant effect on business performance namely > (11.266>1.984) dan (sig  = 0,000< 0,050),Product innovation () has a significant effect on business performance nemely > (3.680>1.984) dan (sig  = 0,000 < 0,050). Simultaneously have a significant effect on business performance. Partially, both market orientation and product innovation variables have a significant effect on business performance namely > (192.273>2.102) dan (sig  = 0.000 < 0,050).Keywoards : market orientation, product innovation, business performance